1970
DOI: 10.1677/joe.0.0480599
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Plasma Progesterone Concentration of Cows During Puberty, Oestrous Cycles, Pregnancy and Lactation, and the Effects of Under-Nutrition or Exogenous Oxytocin on Progesterone Concentration

Abstract: SUMMARY Progesterone concentrations in the peripheral plasma of cows were measured by a protein-binding radioassay method. The mean concentration was lowest at oestrus (0·44 ng/ml) and then increased to a maximum of 6·8 ng/ml about day 14 of the 21-day cycle. The concentration decreased rapidly during the last 4 days of the cycle, reaching low levels on the day before oestrus. There were no significant changes in progesterone concentration during oestrus. After ovariectomy the plasma progesterone conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
63
1
4

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(86 citation statements)
references
References 0 publications
18
63
1
4
Order By: Relevance
“…These results support the view that the release of low levels of progesterone before normal cyclic activity may be important for the development of normal reproductive activity after anoestrus (Donaldson, Bassett & Thorburn, 1970;Yuthasastrakosol, Palmer & Howland, 1975). It is possible that the progesterone has a feedback action on the hypothalamus and/or pituitary to initiate a pattern of gonadotrophin secretion associated with normal cyclic ovarian function.…”
Section: Methodssupporting
confidence: 83%
“…These results support the view that the release of low levels of progesterone before normal cyclic activity may be important for the development of normal reproductive activity after anoestrus (Donaldson, Bassett & Thorburn, 1970;Yuthasastrakosol, Palmer & Howland, 1975). It is possible that the progesterone has a feedback action on the hypothalamus and/or pituitary to initiate a pattern of gonadotrophin secretion associated with normal cyclic ovarian function.…”
Section: Methodssupporting
confidence: 83%
“…1 and in Cows 3 and 4 in Exp. 2 and preceded the onset of normal ovarian and oestrous cycles has been previously noted by a number of workers (Pope, Gupta & Munro, 1969;Donaldson, Bassett & Thorburn, 1970;Robertson, 1972;Tribble et al, 1973;Lamming & Bulman, 1976). The origin of this transient increase in peripheral plasma progesterone is not known, although it has been previously suggested that it originates from luteinized follicles (Tribble et al, 1973).…”
Section: Discussionmentioning
confidence: 73%
“…This is not the case in cavies where plasma progesterone levels during pregnancy can be divided into two phases (see above). (2) The highest progesterone concentration found in the plasma of the guinea-pig and cuis during pregnancy is certainly very much higher than those found in many other animals such as the pregnant hamster (25 ng/ml; Leavitt & Blaha, 1970), ewe (15 to 20 ng/ml; Bassett, Oxborrow, Smith & Thorburn, 1969;Fylling, 1970) and cow (8 ng/ml; Donaldson, Bassett & Thorburn, 1970). Thus, not to mention the high level of 513 ng/ml, even the progesterone concentrations (6-3 to 15 ng/ml) during the first 15 days in guinea-pigs Challis et al, 1971) and in G. musteloides (23 to 60 ng/ml) are, in fact, high levels and the progesterone requirement during the first 15 days' gestation in both species of cavy is, therefore, by no means low compared to these animals.…”
Section: Animals and Sample Collectionmentioning
confidence: 92%